Emergent depth-mechanosensing of epithelial collectives regulates cell clustering and dispersal on layered matrices - Hongsheng Yu; Amit Pathak (Proceedings of the National Academy of Sciences, 2025)
During wound healing, tumor growth, and organ formation, epithelial cells migrate and cluster in layered tissue environments. Although cellular mechanosensing of adhered extracellular matrices is now well recognized, it is unclear how deeply cells sense through distant matrix layers. Since single cells can mechanosense stiff basal surfaces through soft hydrogels of <10 μm thickness, here we ask whether cellular collectives can perform such “depth-mechanosensing” through thicker matrix layers. Using a collagen-polyacrylamide double-layer hydrogel, we found that epithelial cell collectives can mechanosense basal substrates at a depth of >100 μm, assessed by cell clustering and collagen deformation. On collagen layers with stiffer basal substrates, cells initially migrate slower while performing higher collagen deformation and stiffening, resulting in reduced dispersal of epithelial clusters. These processes occur in two broad phases: cellular clustering and dynamic collagen deformation, followed by cell migration and dispersal. Using a cell-populated collagen-polyacrylamide computational model, we show that stiffer basal substrates enable higher collagen deformation, which in turn extends the clustering phase of epithelial cells and reduces their dispersal. Disruption of collective collagen deformation, by either α-catenin depletion or myosin-II inhibition, disables the depth-mechanosensitive differences in epithelial responses between soft and stiff basal substrates. These findings suggest that depth-mechanosensing is an emergent property that arises from collective collagen deformation caused by epithelial cell clusters. This work broadens the conventional understanding of epithelial mechanosensing from immediate surfaces to underlying basal matrices, providing insights relevant to tissue contexts with layers of varying stiffness, such as wound healing and tumor invasion.